Build then sell and sell then build on building quality / Mansor Mohamed - Mohamed, Mansor (Faculty of Architecture, Planning and Surveying, 2010)
The implementation of Build Then Sell (BTS) concept is a new of concept that is rarely represented in construction industry. Previously Sell Then Build (STB) is a concept that contributes in most of residential development area in Malaysia. By the implementation of BTS concept it can reduce the cases of abandoned project. Previously there are many abandoned project in Malaysia and many buyer in Malaysia are cheated by the developer especially those developers who are using the STB concept. Others of buyer complaint about quality of their building are low because the defect was occur at a new building after get of permission by local authority. Now issue relating by the abandoned project and complain about quality are most rarely to hear again especially after implementing of BTS concept. What is the factor influence those situation. Thus, how long of BTS concepts is better than STB concepts and what is the advantages and disadvantages of each concept benefit for buyers regarding by the previous issue and how could be benefit for developers itself.